APPLICATIONWEB SITE BAND "DREAMCHASER"WITH USING ADOBE DREAMWEAVER CS3 - I GdeMade Reichido Dwikaprana (Jurnal Manajemen Informatika, 2010)
The rapid development of the computer becomes a facilitator for information. Internetis one way to get information. With the Internet one can get the right information inorder without spending a huge cost. In addition, the Internet can also be used as a meansof promotion. This site ismade so that more people know about the band "DreamChaser".